2002
DOI: 10.1034/j.1600-0447.2002.01248.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive‐based measures screening for depression in the medically ill: the DMI‐10 and the DMI‐18

Abstract: Objective: We suggest that the identification of depression in the medically ill (DMI) might be improved by focussing on cognitive features. Method: We recruited 302 patients to complete our provisional cognitive‐based measure. Subsets also completed one of two comparator screening measures, either the Hospital and Anxiety Depression Scale (HADS) or the Beck Depression Inventory for Primary Care (BDI‐PC). One hundred and sixty patients were then assessed by a psychiatrist who estimated whether they were `clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 11 publications
4
52
0
1
Order By: Relevance
“…This underlines the central role of cognitive symptoms and depressed mood in any attempt to screen accurately for depression in somatic patients (Parker et al, 2002;Clark et al, 1998). These results provide additional confirmation of the value of using anxiety symptoms when measuring depression and are consistent with studies in the medically ill suggesting that HAD-A performs well in screening for depression (Strik et al, 2001;Katz et al, 2004).…”
Section: Discussionsupporting
confidence: 74%
“…This underlines the central role of cognitive symptoms and depressed mood in any attempt to screen accurately for depression in somatic patients (Parker et al, 2002;Clark et al, 1998). These results provide additional confirmation of the value of using anxiety symptoms when measuring depression and are consistent with studies in the medically ill suggesting that HAD-A performs well in screening for depression (Strik et al, 2001;Katz et al, 2004).…”
Section: Discussionsupporting
confidence: 74%
“…Patients additionally completed the Mood Assessment Programme or MAP (Parker et al, 2008), a computerised tool assessing a range of features including socio-demographic, mood disorder and treatment history details. The MAP also contains a number of validated self-report measures of depressive symptomatology, including the Depression in the Medically Ill-10 measure (DMI-10; Parker et al, 2002), the Severity of Depressive Symptoms measure (SDS; Parker et al, 2009; and the Sydney Melancholia Prototype Index SMPI (Parker et al, 2012(Parker et al, , 2013b. All measures are detailed shortly.…”
Section: General Overviewmentioning
confidence: 99%
“…The DMI-10 (Parker et al, 2002) was designed to detect state depression severity in patients with medical disorders, and to respect and redress concerns that such patients might score falsely high on somatic symptoms such as insomnia, fatigue and weight loss (due to their medical illness rather than concomitants of depression), and so comprises 10 non-somatic depressed mood constructs. Scores for each item range from 0-3, with total scores ranging from 0-30 (a score of 9 or above being identified as indicative of 'clinical depression').…”
Section: Overview Of Depression Measuresmentioning
confidence: 99%
“…Hallahan et al (126) also found a beneficial effect of EPA þ DHA supplementation on the presence or absence of suicidal ideation. However, one study also found no improvement in depression ALA, a-linolenic acid; DPA, docosapentaenoic acid; LA, linoleic acid; AA, arachidonic acid; C, clinical; BDI, Beck Depression Inventory (53) ; PCPG, plasma choline phosphoacylglycerols; þ, positive correlation; x, no correlation; HDRS, Hamilton Depression Rating Scale (93) ; CE, plasma cholesteryl esters; PL, plasma phospholipids; EM, erythrocyte membranes; 2, negative correlation; DMI-18, Depression in the Medically Ill (eighteen-item version) (94) ; NC, non-clinical; ZSDS, Zung Self-Rating Depression Scale (84) ; AT, adipose tissue; CES-D, Center for Epidemiologic Studies (depression scale) (57) ; GDS-15, Geriatric Depression Scale (fifteen-item version) (85) ; EPDS, Edinburgh Postnatal Depression Scale (58) ; IBS, irritable bowel syndrome; SCL, Symptom Checklist (ninety-item version) (95) ; HADS-D, Hospital Anxiety and Depression Scales (depression scale) (55) ; MADRS, Montgomery -Asberg Depression Rating Scale (96) ; mol*, concentration calculated with references to the internal standard 18-methylnonadecanoic acid; SIS, Suicide Intent Scale (97) ; L, plasma lipids.…”
Section: Trial Evidencementioning
confidence: 99%